Comparison of Immersion Time between Strawberry (Fragaria x ananassa) Juice and 35% Carbamide Peroxide on Tooth Discoloration - Puspita, Sartika; Rahmawan, Dinda Tri; Wijayaningrum, Khen Swara (Universitas Muhammadiyah Yogyakarta, 2018)
Tooth color is one of the aesthetic problems in society. This condition is influenced by extrinsic and intrinsic factors. 35% Carbamide peroxide is an ingredient approved by the American Dental Association (ADA) as safe and effective tooth whitening. Strawberry (Fragaria x ananassa) is a natural substance containing ellagic acid that can be used for tooth whitening. The purpose of this study is to determine the tooth discoloration after the immersion of F. x ananassa juice 100% and 35% carbamide peroxide. The method of this research was a pure laboratory experiment. The sample used was 24 premolar postpartum teeth which had been discolored using tea. The specimens were divided into 2 groups, the first group was immersed with F. x ananassa juice 100% and the second group was immersed with 35% carbamide peroxide, respectively for 30, 60, and 90 minutes. The color of the immersed teeth was then measured by a spectrophotometer and a shade guide to determine the color change before and after the treatment. Data were analyzed using Two Way ANOVA and Kruskal-Wallis test. The results of this study indicated that the immersion of F. x ananassa juice 100% was able to make the teeth become brighter, with the same level of brightness using 35% carbamide peroxide. The conclusion of this research was F. x ananassa juice can be used as an alternative material for tooth whitening.Â